2004
DOI: 10.1002/mrc.1417
|View full text |Cite
|
Sign up to set email alerts
|

1H and 13C NMR signal assignment of benzylisoquinoline alkaloids from Fumaria officinalis L. (Papaveraceae)

Abstract: The NMR signal assignments of a series of structurally divergent benzylisoquinolines isolated from Fumaria officinalis L. (Fumariaceae, Papaverales), namely adlumine, corlumine, corydamine, cryptopine, fumarophycine, O-methylfumarophycine, hydrastine, parfumine, protopine and sinactine, are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
20
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 27 publications
10
20
0
1
Order By: Relevance
“…The long range gHMBC correlation established the C→H and H→C cross-correlations among the H and C-atoms ( The other five known alkaloids were identified as protopine (2), norsanguinarine (3), dihydrosanguinarine (4), 6-methoxydihydrosanguinarine (5) and oxysanguinarine (6) ( C-NMR spectroscopic data agreed with those reported (Takahashi et al, 1985;Seger et al, 2004;Wangchuk et al, 2010). It was the major component of the plant.…”
Section: Separation/isolation Of Alkaloidssupporting
confidence: 83%
“…The long range gHMBC correlation established the C→H and H→C cross-correlations among the H and C-atoms ( The other five known alkaloids were identified as protopine (2), norsanguinarine (3), dihydrosanguinarine (4), 6-methoxydihydrosanguinarine (5) and oxysanguinarine (6) ( C-NMR spectroscopic data agreed with those reported (Takahashi et al, 1985;Seger et al, 2004;Wangchuk et al, 2010). It was the major component of the plant.…”
Section: Separation/isolation Of Alkaloidssupporting
confidence: 83%
“…C-NMR, and LC-IT TOF MS data with the literature values to be menisdaurin (1) (Seigler et al 2005), menisdaurilide (2) (Audran and Mori 1998), trans-N-p-coumaroyltyramine (3) (Kim et al 2014), trans-N-p-feruloyltyramine (4) (Choi et al 2016), 4-Oferuloylquinicacid (5) (Ge et al 2007), chlorogenic acid (6) (Han et al 2006), 3-O-feruloylquinicacid (7) (Ge et al 2007), ferulic acid (8) (Han et al 2006), protopine (9) (Seger et al 2004), Kaempferol 3,7-di-O-β-D-glucopyranoside (10) (Lee et al 2009 , α-rhamnoisorobin (12) (Cha and Lee 2007), astragalin (13) (Seo et al 2016), and nicotiflorin (14) (Tran et al 2014). Compound 1, 3-8, and 10-14 were reported for the first time from this plant.…”
supporting
confidence: 52%
“…The available data indicate that G. parviflora contains fumaric acid (Mostafa, Abd El-Aziz, Hafez, & El-Shazly, 2013), essential oil (Mostafa et al, 2013;Pino et al, 2010), phytosterols (Mostafa et al, 2013;Tariq et al, 2008), mineral salts (Odhav, Beekrum, Akula, & Baijnath, 2007) and vitamins (Grubben & Denton, 2004), whereas F. officinalis fumaric and malic acids (Bradley, 1992;Ivanov et al, 2014;Soušek et al, 1999), isoquinoline alkaloids (Seger, Sturm, Strasser, Ellmerer, & Stuppner, 2004;Soušek et al, 1999;Sturm et al, 2006;Suau, Cabezudo, Rico, Nájera, & López-Romero, 2002) and indenobenzazepines (Bradley, 1992;Newall, Anderson, & Phillipson, 1996), as well as mucilage, resin, and bitter principles (Newall et al, 1996) have been identified.…”
Section: 3mentioning
confidence: 94%